Chapter 18: Handling, Cooling and Sanitation Techniques for Maintaining Postharvest Quality - Steven A. Sargent; Mark A. Ritenour; Jeffrey K. Brecht (EDIS)
This chapter focuses on methods and techniques for reducing losses in postharvest quality during typical commercial handling operations. This document is HS719, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.